1994
DOI: 10.4050/jahs.39.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Around a Rotor Blade Excited in Pitch, Part 1: Dynamic Inflow

Abstract: This is the first of two papers describing experiments on a two-bladed rotor in hover, under controlled pitch excitation. Measurements of the inflow to the rotor are described, first under steady conditions, and then under prescribed 4-per-rev pitch excitation. The high data rates, data acquisition techniques and data quality required for this experiment are demonstrated, including 4-per-rev velocity variations due to 1-degree pitch oscillation, extracted over a single period of rotor revolution at 600rpm. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…The existing body of experimental work is comprised primarily of studies utilizing single-point velocity measurement techniques in the wake of a single rotor. Liou [7] investigated the inflow response of a rotor to sinusoidal collective pitch inputs of 1 • amplitude at four times the rotor rotational frequency (4/rev) using laser doppler velocimetry (LDV). Measurements of axial velocity were taken along the 45 • radial line at axial locations of 4% and 10% radius above the rotor plane.…”
Section:  mentioning
confidence: 99%
“…The existing body of experimental work is comprised primarily of studies utilizing single-point velocity measurement techniques in the wake of a single rotor. Liou [7] investigated the inflow response of a rotor to sinusoidal collective pitch inputs of 1 • amplitude at four times the rotor rotational frequency (4/rev) using laser doppler velocimetry (LDV). Measurements of axial velocity were taken along the 45 • radial line at axial locations of 4% and 10% radius above the rotor plane.…”
Section:  mentioning
confidence: 99%
“…Work by Liou' 22 ' who examined the induced flow response over a radial range at just one excitation frequency, revealed a hysteresis effect when the induced flow at a point is plotted against the excitation root pitch. It was also found that this hysteresis effect diminished towards the tip and seemed to be predominantly affected by the inboard shed vorticity.…”
Section: / "mentioning
confidence: 99%